Characteristics of β-type Ti-41Nb alloy produced by laser powder bed fusion: Microstructure, mechanical properties and in vitro biocompatibility. (10th October 2022) - Li, Zhongjie; Qiu, Jiajun; Xu, Hao; Dong, Anping; He, Lin; Zhu, Guoliang; Du, Dafan; Xing, Hui; Liu, Xuanyong; Sun, Baode
Highlights: β-type Ti-41Nb alloy has been fabricated by laser powder bed fusion (l -PBF) using pre-alloyed powder. l -PBFed Ti-41Nb alloy exhibits excellent strength-ductility synergy. l -PBFed Ti-41Nb alloy shows better cell biocompatibility compared with CP-Ti. Abstract: A β-type Ti-41Nb alloy with high relative density has been successfully fabricated by laser powder bed fusion (l -PBF) using pre-alloyed powders for potential implant application. The homogeneous microstructure can be achieved in l -PBF fabricated (l -PBFed) Ti-41Nb alloy but slight composition segregation was detected along molten pool boundaries. The l -PBFed alloy was dominated by typical epitaxial columnar grains with strong 〈001〉 grain orientation along building direction (BD), and cellular structure was distinguished within the columnar grains. The main reasons for this microstructure can be attributed to effective thermal gradient and epitaxial growth. l -PBFed alloy exhibited higher mechanical strength compared with cold rolling plus annealing (CRA) alloy due to the finer grains, dislocations accumulation and different TRIP behaviors, accompanied by good ductility. It also exhibited much lower thermal conductivity and better hydrophilic feature than those of CP-Ti. Besides, the l -PBFed alloy exhibited slightly better cell spread and cell proliferation rates compared with CP-Ti. Moreover, l -PBFed alloy presented better alkaline phosphatase (ALP) activities and extracellular matrix (ECM) mineralization, which suggests that the l -PBFed alloy can stimulate the osteogenic differentiation of rat bone mesenchymal stem cells. The Ti-41Nb alloy, fabricated by l -PBF, reveals a good combination of mechanical properties, physicochemical properties and biocompatibility, exhibiting the great potential as the dental implant. Graphical abstract: Image, graphical abstract